The Use of Alginate in Lemon Extract Effervescent Powder Production - M. Murdinah (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2015)
Study on the use of alginate in lemon (Citrus medica var lemon) extract effervescentpowder production has conducted. The aims of the research are to determine the optimumconcentration of alginate used in lemon extract effervescent powder to produced bestproduct and acceptance consumen.The lemon extract effervescent powder formulaconsisted of lemon extract powder, sucrose, aspartame, salt and effervescent mix (citricacid-tartrat acid-sodium bicarbonat). The alginate used in this study was extracted fromSargassum filipendula sea weed. The concentration of alginate used in lemon effervescentpowder production was varied from 1; 2; 3 and 4%. The parameters observed to see thequality of the product were moisture content, ash content, pH, viscosity and organoleptic of dietary fiber, sugar content, vitamin C content, total titratable acids, TPC and E.Colito the best product. The result showed that the higher the concentration of alginate usedin lemon effervescent powder production, the higher viscousness and the lower theorganoleptic value. The optimum concentration of alginate used in the lemon extracteffervescent powder processing was 1%. The characteristic this product 7.60% moisturecontent, 0.86% insoluble dietary fiber , 7.92% soluble dietary fiber, 3.74% sugar content,55,26 mg/100 g vitamin C, 134.15 mL 0.1 NaOH/100 mL total titratable acids, 20 cPsviscosity, <2.5x102 coloni/mL TPC and E.Coli negative.Keywords: Alginate, characteristic, effervescent powder, lemon extract